Nine key elements for fitness (Peak Performance, 2005)
One of the misconceptions in the sports world is that a sportsperson gets in shape by just playing or taking part in his/her chosen sport. If a stationary level of performance, consistent ability in executing a few limited skills, is your goal then engaging only in your sport will keep you there. However, if you want the utmost effciency, consistent improvement, and balanced abilities sportsmen and women must participate in year round conditioning programs. The bottom line in sports conditioning and fitness training is stress. Not mental stress, but adaptive body stress. Sportsmen and women must put their bodies under a certain amount of stress to increase physical capabilities. Exercise scientists have identifed that fitness comprises of nine key elements. The following lists each of the nine elements and an example of how they are used: Strength - the extent to which muscles can exert force by contracting against resistance (holding or restraining an object or person) - Power - the ability to exert maximum muscular contraction instantly in an explosive burst of movements (jumping or sprint starting) - Agility - the ability to perform a series of explosive power movements in rapid succession in opposing directions (zigzag running or cutting movements) - Balance - the ability to control the body`s position, either stationary (eg a handstand) or while moving (eg a gymnastics routine) - Flexibility - the ability to achieve an extended range of motion without being impeded by excess tissue, ie fat or muscle (Executing a leg split) - Local Muscle Endurance - a single muscle`s ability to perform sustained work (rowing or cycling) - Cardiovascular Endurance - the heart`s ability to deliver blood to working muscles and their ability to use it (running long distances) - Strength Endurance - a muscle`s ability to perform a maximum contracture time after time (continuous explosive rebounding through an entire basketball game) - Co-ordination - the ability to integrate the above listed components so that effective movements are achieved. Of all the nine key elements of fitness cardiac respiratory qualities are the most important to develop as they enhance all the other components of the conditioning equation. As a long-time UK Athletics coach, I have always been aware that advice at this level has been expensive and often difficult to obtain. This workbook solves the problems of cost and inconvenience in obtaining expert coaching guidance. On the following pages you will find evidence-based advice based on £ millions worth of trials conducted by dedicated sports scientists, with comprehensive, science based workouts designed to enhance your performance for your sport or event.